Potret Penghulu dalam naskah; Sebuah pengalaman penelitian - Hisyam, Muhamad (UI Scholars Hub, 2005)
In the daily life of the Indonesian people, a penghulu plays a role in accordance with the way the word is understood by the community in which he lives. In West Sumatra, a penghulu is the head of the nagari. In Riau, he has a status equal to that of a head of a village. In Java, he has an authority in all administrative matters of religion. This paper discusses the meaning of penghulu as depicted in old manuscripts written by the natives. Based on a research on these native manuscripts, it can be concluded that a penghulu plays the roles of both a bureaucrat and a Muslim leader.